Analysis of the influence of dabigatran on coagulation factors and inhibitors. (25th June 2014) - Tsutsumi, Y.; Shimono, J.; Ohhigashi, H.; Ito, S.; Shiratori, S.; Teshima, T.
Summary Introduction Dabigatran is an oral intake thrombin inhibitor for preventive administration against stroke accompanied by atrial fibrillation. Although dabigatran causes prolonged activated partial thromboplastin time (APTT), the effect of dabigatran on each coagulation factor and coagulation factor inhibitor remains to be investigated. Our aim was to analyze the influence of dabigatran on coagulation factors and coagulation factor inhibitors. Methods We administered dabigatran to 40 patients. In 26 of these 40, we analyzed the activity of several coagulation factors and their inhibitors. We used Fisher's exact test to determine statistical significance. Results The activities of many coagulation factors changed during the dabigatran therapy. Factor II levels decreased in all patients showing prolongation of partial thromboplastin (PT) and APTT. The antifactor VIII inhibitor was positive in the majority of patients with prolonged PT and APTT, while activities of protein C, protein S, and antifactor IX inhibitor were not associated with PT and APTT prolongation. Conclusion Dabigatran affects the activities of many coagulation factors, including factors II, V, VIII, and IX, as well as the antifactor VIII inhibitor.